The Concept of Communication the Renewal of Muhammad Abduh's Thought and Its Relevance in Islamic Education Management Contemporary Era - Hidayatullah, Iis Anugrah Rahmat (EDUMALSYS Journal of Research in Education Management, 2023)
Renewal is a necessity that the world is always changing from time to time, and Islamic Education Management is no exception. Good management will deliver quality Islamic Education Institutions (better), quality Islamic Education Institutions will produce perfect students. The perfect student is one who has advanced intellect and strong aqedah. According to Abduh, Islamic educational institutions must have a guarantor that can bridge two major cultural products in the world, namely Islam and the West. This research is important because it tries to reconstruct Muhammad Abduh's thoughts on the points of renewal and their relevance to Islamic Education Management, then critically analyzed through a historical philosophical approach to find out the extent to which Muhammad Abduh's thoughts imprinted in the Contemporary era in the context of Islamic Education Management.